1982
DOI: 10.1007/bf00343996
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mental illness on the emotional experience of music

Abstract: Psychiatric patients (N=107) were studied regarding the importance of pertaining to a diagnostic group for the variation of emotional experience in music. The diagnostic groups chosen were: schizophrenic, depressive and manic psychosis, obsessive, depressive, anxiety and hysterical neurosis. As stimuli seven newly composed pieces of music orchestrated for a small symphony orchestra were used. The assessment of emotional experience was accomplished by semantic differential scales measuring the factors tension-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In both groups, participants were exposed to seven pieces of orchestral music and their emotional experiences were measured using the three-factor semantic differential scales. OCD patients rated all music more intensely compared to healthy subjects, as well as patients with other psychiatric illnesses [63]. Despite the finding of enhanced sensitivity in OCD patients, their representation in the studies was relatively small, with only 12 patients with OCD among 107 participants.…”
Section: Music Perception and Musical Obsessions In People With Ocdmentioning
confidence: 89%
See 3 more Smart Citations
“…In both groups, participants were exposed to seven pieces of orchestral music and their emotional experiences were measured using the three-factor semantic differential scales. OCD patients rated all music more intensely compared to healthy subjects, as well as patients with other psychiatric illnesses [63]. Despite the finding of enhanced sensitivity in OCD patients, their representation in the studies was relatively small, with only 12 patients with OCD among 107 participants.…”
Section: Music Perception and Musical Obsessions In People With Ocdmentioning
confidence: 89%
“…Nielzen and Cesarec [62,63] showed that people diagnosed with OCD are more emotionally responsive to music than healthy subjects [62] and experience more tension when listening to music compared to patients with schizophrenic, affective and anxiety disorders. [63].…”
Section: Music Perception and Musical Obsessions In People With Ocdmentioning
confidence: 99%
See 2 more Smart Citations